Cardiac autonomic and haemodynamic recovery after a single session of aerobic exercise with and without blood flow restriction in older adults. Issue 24 (17th December 2017) - Ferreira, Marina Lívia Venturini; Sardeli, Amanda Veiga; Souza, Giovana Vergínia De; Bonganha, Valéria; Santos, Lucas Do Carmo; Castro, Alex; Cavaglieri, Cláudia Regina; Chacon-Mikahil, Mara Patrícia Traina
ABSTRACT: This study investigated the autonomic and haemodynamic responses to different aerobic exercise loads, with and without blood flow restriction (BFR). In a crossover study, 21 older adults (8 males and 13 females) completed different aerobic exercise sessions: low load without BFR (LL) (40% VO2 max ), low load with BFR (LL-BFR) (40% VO2 max + 50% BFR) and high load without BFR (HL) (70% VO2 max ). Heart rate variability and haemodynamic responses were recorded during rest and throughout 30 min of recovery. HL reduced R–R interval, the root mean square of successive difference of R–R intervals and high frequency during 30 min of recovery at a greater magnitude compared with LL and LL-BFR. Sympathetic–vagal balance increased the values for HL during 30 min of recovery at a greater magnitude when compared with LL and LL-BFR. Post-exercise haemodynamic showed reduced values of double product at 30 min of recovery compared to rest in LL-BFR, while HL showed higher values compared to rest, LL-BFR and LL. Reduced systolic blood pressure was observed for LL-BFR (30 min) compared to rest. Autonomic and haemodynamic responses indicate lower cardiovascular stress after LL-BFR compared to HL, being this method, besides the functional adaptations, a potential choice to attenuate the cardiovascular stress after exercise in older adults.